EVALUASI COAL RECOVERY PADA KEGIATAN PENAMBANGAN DARI PIT A MENUJU STOCKPILE DI PT. X (EVALUATION OF COAL RECOVERY IN MINING ACTIVITIES FROM PIT A TO STOCKPILE AT PT. X) - Azzahra, Siti Maghfirah; Hasan, Harjuni; Oktaviani, Revia; Winarno, Agus; Respati, Lucia Litha (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2022)
Several coal companies apply a minimum target of coal recovery. Coal recovery is a comparison between the actual tonnage of coal production based on the data from the weighbridge and the coal tonnage as a result of survey measurements expressed as a percentage. The greater the coal recovery more effective the coal was mined. Loss of coal during the mining process was unavoidable. However, if the cause is known in detail, the amount of loss can be minimized by making efforts to repair the existing causes and can increase the value of coal recovery and the utilization of coal reserves owned by the company. There are 30 coal mining data. 19 of them still had a coal recovery below 96% with a total tonnage loss of 1.485,97 tonnes. There are 6 activity criteria that cause coal recovery, including the coal getting less than optimal and still leaves coal on front which accounts for 47,45% of the total loss, coal used as road coating accounts for 5,67%, survey measurement data is less representative the appearance of coal shapes accounted for 2,48%, errors naming on coal haulage coupons accounted for 9,77%, waterlogged fronts accounted for 29,64%, and recleaning accounted for 5,01% of the total tonnage loss.